Pengaruh Media Exposure, Profitabilitas, dan Green Accounting terhadap Corporate Social Responsibility Disclosure pada Perusahaan Sektor Kesehatan yang Terdaftar di Bursa Efek Indonesia Periode 2021-2024 - Novi Jelpiani M. Hutagalung; Mulatua P. Silalahi; Merry Anna Napitupulu; Sahala Purba (Universitas Methodist Indonesia, 2026)
This study aims to determine the effect of media exposure, profitability, and green accounting on corporate social responsibility disclosure partially and simultaneously. The sample selection criteria used were purposive sampling with a population of 38 companies, resulting in 12 samples. In this study, the dependent variable used was Corporate Social Responsibility Disclosure, while the independent variables were Media Exposure, Profitability, and Green Accounting. The data analysis method used was multiple linear regression analysis with SPSS 26. The results showed that partial media exposure had a negative and significant effect on corporate social responsibility disclosure, profitability had a positive but insignificant effect on corporate social responsibility disclosure, and green accounting had a negative and insignificant effect on corporate social responsibility disclosure. Simultaneously, media exposure, profitability, and green accounting had a significant effect on corporate social responsibility disclosure listed on the Indonesia Stock Exchange. The coefficient of determination test (adjusted R squared) for this regression model shows a value of 0.203, or 20.3%. This indicates that the variables Media Exposure, Profitability, and Green Accounting only explain 20.3% of the Corporate Social Responsibility Disclosure variable, while the remaining 79.7% is influenced by other variables not included in this study's regression model.